Pengaruh Tingkat Pendidikan, Thin Capitalization, Kepemilikan Institusional Terhadap Penghindaran Pajak - Salsabila Rachmasari Suharto; Hermi Hermi (Ikatan Da'i Indonesia, 2026)
The objective of this research is to examine the factors influencing tax avoidance. Using a purposive sampling method, the study initially identified 110 samples. After removing 17 outliers, a final sample of 93 observations was obtained from banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The research data were sourced from audited financial statements and annual reports accessible through the official IDX website and the respective companies' websites. The data were analyzed using multiple linear regression analysis, processed with the SPSS (Statistical Program for Social Science) software. The results of this research indicate that: (1) CFO Education has a negative effect on Tax Avoidance; (2) Thin Capitalization has a positive effect on Tax Avoidance; and (3) Institutional Ownership has a negative effect on Tax Avoidance.